2021
DOI: 10.14309/ctg.0000000000000401
|View full text |Cite
|
Sign up to set email alerts
|

Post-Induction High Adalimumab Drug Levels Predict Biological Remission at Week 24 in Patients With Crohn's Disease

Abstract: INTRODUCTION: We investigated whether early adalimumab drug levels (ADL) at week 4 predicted biological remission at week 24. METHODS: In a prospective study, we assessed clinical and biological remission at weeks 0, 4, 12, and 24 after induction of adalimumab in 33 patients with Crohn's disease. Disease activity was determined by the Harvey-Bradshaw Index, ileocolonoscopy reports, cross-sectional imaging, C-reactive protein (CRP), and fecal calprotectin (FC) levels. Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
1
0
0
Order By: Relevance
“…This initial study suggests higher concentrations may be needed to achieve deeper levels of remission. Another study showed that adalimumab drug concentrations >13.9 ug/mL at week 4 were associated with serological remission at week 24, consistent with emerging literature suggesting that higher concentrations of anti-TNF therapy may be needed to achieve a response [28,29].…”
Section: Introductionsupporting
confidence: 71%
“…This initial study suggests higher concentrations may be needed to achieve deeper levels of remission. Another study showed that adalimumab drug concentrations >13.9 ug/mL at week 4 were associated with serological remission at week 24, consistent with emerging literature suggesting that higher concentrations of anti-TNF therapy may be needed to achieve a response [28,29].…”
Section: Introductionsupporting
confidence: 71%